TEOLOGI LINGKUNGAN: PERSPEKTIF KEAGAMAAN DALAM PELESTARIAN ALAM - Suyitno, Suyitno; Zulfa, Maulida Indana (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2024)
This study aims to analyze the integration of environmental theology concepts and values into the religious training system at Balai Diklat Keagamaan Denpasar and to identify the supporting and inhibiting factors in its implementation. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the Miles and Huberman interactive model. The findings reveal that environmental theological values such as khalifah (stewardship), trust (amanah), prohibition of environmental destruction (fasad), and the principle of rahmatan lil ‘alamin have been substantively integrated into training materials, particularly through religious moderation perspectives and reflective learning methods. Supporting factors include strong normative religious foundations, the paradigm of religious moderation, participatory learning approaches, and Bali’s socio-religious context that promotes harmony with nature. Inhibiting factors include the absence of an explicit eco-theology curriculum, limited ecological literacy among trainers, time constraints within the training structure, and the lack of measurable ecological behavior indicators. The study concludes that institutional strengthening through thematic eco-theology curriculum development and capacity building of human resources is essential to establish a religious training system that is responsive to environmental crises.